Teachers’ Efforts to Implement Problem-Based Learning in Order to Improve Students’ Collaboration and Communication Skills - Lusia Mumtahana; Cicik Nur Rosyidah; Shakila Kausar; Nur Khamim; Moh. Syamsi (At-tadzkir: Islamic Education Journal, 2026)
This study aims to analyse teachers’ efforts in implementing the Problem-Based Learning model to enhance students’ collaboration and communication skills in the Aqidah Akhlak subject at MA Ath-Thohiriyyah Blawirejo. The study employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The research subjects included the principal, the vice principal for curriculum affairs, the Aqidah Akhlak teacher, the Geography teacher, and eleventh-grade students. The findings indicate that implementing Problem-Based Learning effectively enhances social interaction, promotes active participation, and fosters students’ sense of responsibility through group discussions, presentations, evaluations, and reflection activities. The model was implemented in five stages: problem identification, group formation, investigation, presentation of findings, and evaluation and reflection. The study also identified several challenges, including students’ low self-confidence during presentations and limited instructional time. These challenges were addressed by providing motivation, active guidance, and systematic time management. Overall, the findings demonstrate that Problem-Based Learning significantly enhances students’ collaboration and communication skills in Aqidah Akhlak learning.